Logophagies: the voice of the "mystical" silence of the "poetic reason" in poetry by José Verón Gormaz - Soria Caro, Jesús (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper studies the influence on the poetry of José Verón Gormaz of the thought of María Zambrano, paying special attention to the link that she proposes between philosophy and poetry. Starting from this link, the paper analyzes the poetics of silence, one of the logophagic figures of modern poetics.
Keywords: María Zambrano; José Verón Gormaz; poetic reason; poetics of silence; logophagies